Studi Evaluasi Ketersediaan Lahan Parkir dalam Menentukan Kapasitas Kendaraan di Pasar Tradisional Sendangrejo Ngimbang - Dani Fariansa; Ahmad Ridwan; Rio Rahma Dhana (Jurnal Talenta Sipil, 2026)
Sendangrejo Ngimbang Market is one of the traditional markets with relatively high activity in Ngimbang District. Market visitors come not only from the surrounding area but also from other districts, such as Sambeng, Bluluk, and Sukorame. These activities generate a demand for parking space that needs to be evaluated to prevent disruption to traffic flow around the market area. This study aims to evaluate the availability of parking space in determining vehicle capacity at Sendangrejo Ngimbang Traditional Market. A quantitative method was applied through a field survey conducted over 7 observation days on January 4, 6, 11, 13, 22, 25, and 31, 2026, from 07:00 to 12:00 WIB. The analyzed parameters included parking accumulation, parking duration, parking volume, parking index, and parking turnover rate. The results showed that the highest motorcycle parking accumulation during the observation period was 66 vehicles out of a capacity of 165 vehicles, while the highest car parking accumulation was 4 vehicles out of a capacity of 4 vehicles. The highest motorcycle parking index was 40.00%, whereas the highest car parking index reached 100.00% on one observation day. Therefore, motorcycle parking space remains sufficient, while car parking reaches full capacity at certain times. Accordingly, better car parking arrangement, separation of parking areas by vehicle type, and control of on-street parking are required to prevent market activities from disrupting surrounding traffic flow.